Superficial CD34-positive fibroblastic tumor: Report of an extremely rare entity - Ebru Zemheri; Ayşe Serap Karadag; İsmail Yılmaz (Wolters Kluwer Medknow Publications, 2020)
Superficial CD34-positive fibroblastic tumor (SCPFT), a newly described neoplasm is a rare mesenchymal neoplasm of intermediate malignancy. A 63-year-old man presented with a painless, slow-growing, skin-colored nodule of 8 × 4 mm in diameter on the right side of the neck. It was completely resected. Histologically, a tumor located in the subcutis with the minimally infiltrative pattern was detected. The tumor was composed of variably enlarged bizarre and pleomorphic spindle to polygonal cells. Tumor cells were stained strongly diffuse positive with CD34 and weak positive with keratin, negative with STAT6, FLI-1, ERG, S100, desmin, and smooth muscle actin. The fluorescence in-situ hybridization (FISH) analysis was negative for COL1A1 gene rearrangement. As per the findings, the case was diagnosed as a SCPFT. It is a borderline mesenchymal neoplasm occurring within the superficial soft tissues with distinctive morphological and immunohistochemical features.